2022
DOI: 10.1101/2022.07.14.22277638
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic potential of IL6R blockade for the treatment of sepsis and sepsis-related death: Findings from a Mendelian randomisation study

Abstract: Introduction Sepsis is characterised by dysregulated, life-threatening immune responses, which are thought to be driven by cytokines such as interleukin-6 (IL-6). Genetic variants in IL6R known to downregulate IL-6 signalling are associated with improved COVID-19 outcomes, a finding later confirmed in randomised trials of IL-6 receptor antagonists (IL6RA). We hypothesised that blockade of IL6R could also improve outcomes in sepsis. Methods We performed a Mendelian randomisation analysis using single nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…5 This trial evidence was predated by genetic studies using instrumental variable approaches (Mendelian randomisation 6 ) that identified carriers of certain single nucleotide polymorphisms (SNPs) in the IL-6 receptor gene (IL6R) were relatively protected from severe COVID-19, a finding replicated in multiple independent cohorts. [7][8][9][10] Recent similar studies also identified the same protective effect in sepsis, where variants in IL6R were again found to be protective against the development of sepsis, admission to critical care with sepsis, and death with sepsis. 8 Given the trial evidence of effectiveness in COVID-19, and supporting genetic evidence in sepsis, we aimed to interrogate whether IL-6 downregulation might also lead to improved outcomes in severe malaria, and whether this might represent a common target for severe infection.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…5 This trial evidence was predated by genetic studies using instrumental variable approaches (Mendelian randomisation 6 ) that identified carriers of certain single nucleotide polymorphisms (SNPs) in the IL-6 receptor gene (IL6R) were relatively protected from severe COVID-19, a finding replicated in multiple independent cohorts. [7][8][9][10] Recent similar studies also identified the same protective effect in sepsis, where variants in IL6R were again found to be protective against the development of sepsis, admission to critical care with sepsis, and death with sepsis. 8 Given the trial evidence of effectiveness in COVID-19, and supporting genetic evidence in sepsis, we aimed to interrogate whether IL-6 downregulation might also lead to improved outcomes in severe malaria, and whether this might represent a common target for severe infection.…”
Section: Introductionmentioning
confidence: 68%
“…This evidence is suggestive that IL-6 is not causal, and should be taken in the context that variants that alter IL-6 signalling do alter both the incidence and outcomes of other infections, and that trial evidence of IL-6 inhibition has supported the genetic evidence in COVID-19. 7,8,35 However, we would caution overinterpretation of our null result to suggest IL-6 is irrelevant in severe malaria, although it does weaken the case for suggestion of IL-6 inhibition as a therapeutic option.…”
Section: Limitationsmentioning
confidence: 77%
See 3 more Smart Citations